Conceptualizing and researching governance in public and non-profit organizations - Gnan, Luca.; Hinna, Alessandro; Monteduro, Fabio (Bingley, U.K. : Emerald, 2013)
The first volume of the series aims to give an outline of the state of the art and the most recent research being done on public and non profit governance at the international level (with particular emphasis in Europe). The focus of the volume is mainly on the organizational governance that still remains a neglected area of governance both in the public and in the non-profit sector. The volume includes two groups of chapters aimed at examining the recent trends and the future directions of the public and non-profit governance research. One group of chapters addresses broad issues of how to conceptualize and research 'governance' in public and non-profit organizations. The second group of chapters deals with recent trends of research on governance mechanisms through empirical studies, including contingency and behavioural studies on public and non-profit boards, studies on participative governance mechanisms such as stakeholder involvement and citizens participation and studies on governance codification.
Introduction / Luca Gnan, Alessandro Hinna, Fabio Monteduro -- Unraveling the concept of public governance : a literature review of different traditions / Denita Cepiku -- Organisational governance features, innovation and performance in non-profit organisations : existing evidence and future research directions / Bram Verschuere, Eline Beddeleem -- Leading organisational changes in public sector building blocks in understanding boards behaviour / Luca Gnan, Alessandro Hinna, Danila Scarozza -- Common agency theory, corporate governance, and not-for-profit organizations / Marco Romano -- The movement beyond the new public management : public governance practices in Italian public organisations / Luca Gnan ... [et al.] -- Governance and value creation in grant-giving foundations / Giacomo Boesso, Alessandro Hinna, Fabio Monteduro -- The codification of nonprofit governance : a comparative analysis of Swiss and German nonprofit governance codes / Georg von Schnurbein, Sabrina Stöckli -- The voice of patients and the public in the national health service : issues of implementation / Gianluca Veronesi, Kevin Keasey -- Co-operative governance of public-citizen partnerships : two diametrical participation modes / Richard Lang, Dietmar Roessl, Daniela Weismeier-Sammer.
Print version record
Keywords: Political Science -- Public Policy -- General; Political Science -- General; Political Science -- Public Policy -- Social Policy; Politics & government; Non-profitmaking organizations; Nonprofit organizations